1990
DOI: 10.1093/oxfordjournals.eurheartj.a059685
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of a cardioprotective agent in patients with severe ischaemic cardiomyopathy

Abstract: Trimetazidine (TMZ) has been shown to have anti-ischaemic properties improving exercise tolerance without haemodynamic effects. A 6-month double-blind placebo-controlled study was carried out in 20 patients, mean age 59 +/- 6 years, to examine the benefit of adding 60 mg of TMZ vs placebo to the classical therapy, excluding those previously treated with calcium-antagonists, conversion enzyme inhibitors, vasodilators and antiplatelet agents. All patients had severe ischaemic cardiomyopathy, confirmed by coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 0 publications
4
64
0
6
Order By: Relevance
“…Preliminary clinical studies tend to confirm a direct benefit of a metabolic approach with TMZ in left ventricular dysfunction (Wildhirt et al 1999;Zhao et al 2000;Belardinelli and Purcaro 2001). A significant improvement in ejection fraction was also found with TMZ, compared with placebo, in a group of patients undergoing PTCA (Brottier et al 1990;Birand et al 1998). Recent studies have found that TMZ protects from dobutamine-induced ischemia and improves resting ventricular function (Lu et al 1998;Belardinelli and Purcaro 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Preliminary clinical studies tend to confirm a direct benefit of a metabolic approach with TMZ in left ventricular dysfunction (Wildhirt et al 1999;Zhao et al 2000;Belardinelli and Purcaro 2001). A significant improvement in ejection fraction was also found with TMZ, compared with placebo, in a group of patients undergoing PTCA (Brottier et al 1990;Birand et al 1998). Recent studies have found that TMZ protects from dobutamine-induced ischemia and improves resting ventricular function (Lu et al 1998;Belardinelli and Purcaro 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Beneficial placebo [2][3][4][5] and nifedipine [6]. An unchanged rate x effects have also been reported in ischaemic cardiopressure product at rest and at peak exercise in humans myopathy [10] and during coronary artery bypass surgery [3,4,6], and unchanged coronary blood flow in dogs [7] [11]. Brottier et al [10] reported that trimetazidine suggest that trimetazidine may exert its anti-ischaemic significantly improved clinical status and isotopic ejection Correspondence: Professor J. M. Detry, Saint-Luc University Hospital, Division of Cardiology, 10 avenue Hippocrate, B 1200 Brussels, Belgium fraction, and decreased cardiac volume after 6 months treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a placebo-controlled study Brottier et al. [10] reported that trimetazidine improved clinical status and ejection fraction, and decreased cardiac volume in patients with severe ischaemic cardiomyopathy. In a placebo-controlled study the antiischaemic effects of intracoronary administration of 6 mg trimetazidine were investigated during percutaneous transluminal coronary angioplasty [9].…”
mentioning
confidence: 99%
“…48,49,[55][56][57][58] In several subsequent studies, the similar finding was confirmed, based on both global and regional LV systolic function improvement, as well as the enhancement of LV diastolic function. [48][49][50]59 Furthermore, the improvement of LV remodelling processes and the reduction of the plasma inflammatory response, natriuretic peptides, cardiac troponin levels and a recovery of the endothelium-dependent relaxation of conduit arteries was shown. 48,49,56,59 These results were obtained in HF patients with ischaemic aetiology while no effects of trimetazidine in patients with HF of nonischaemic aetiology was revealed.…”
Section: Trimetazidine In Heart Failurementioning
confidence: 95%
“…Benefical effects include improving NYHA functional class, exercise tolerance, QoL, LVEF and cardiac volumes (see Table 2). [48][49][50][51][52][53][54] Among the first reports was the study of Brottier et al who analysed clinical results with long-term treatment with trimetazidine on top of conventional therapy. 50 After follow up of 6 months, improvement of LVEF by 9.…”
Section: Trimetazidine In Heart Failurementioning
confidence: 99%